PENGARUH EKSTRAK DAUN EKOR NAGA (Rhaphidophora pinnata (L.f) Schott) TERHADAP KADAR MALONDIALDEHID DARAH PADA TIKUS DIABETES YANG INDUKSI ALOKSAN - Fathnur Sani K; Havizur Rahman; Yuliawati Yuliawati; Agung Giri Samudra (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
Ekor Naga (Rhaphidophora pinnata (L.f) Schott) leaves is a traditional medicinal plant that contains secondary metabolites of alkaloids, flavonoids, saponins, and tannins, which have antioxidant effects. Uncontrolled diabetes mellitus will be one of the triggers for high free radicals in the body. This study aims to determine the effect of the effect of ekor naga leaves extract which has potentian as an antioxidant on malondialdehyde levels as a prooxidant marker in alloxan-induced diabetes mellitus rats. The reseaech method used a post test only control group design. The test animals used were 20 animals, each group of 5 test animals. Group 1: Positive Control (Glibenclamide 10 mg/Kg BW), Group 2: Negative Control (Na CMC 0,5%), Group 3: Ekor Naga Leaf Extract 250 mg/Kg BW, and Group 4: Ekor Naga Leaves Extract 500 mg/Kg BW. The data taken is the level of malondialdehyde in the blood. The results were analyzed using One-way ANOVA with a 95% confidence level. The results showed that the ethanolic extract of the ekor naga leaves had a role in reducing Malondialdehyde or lipid peroxide in the blood in diabetic rats where the best dose is 500 mg/Kg with malondialdehyde yield of 0,569 nmol/mL. Followed by a dose of 250 mg/Kg BW with malondialdehyde value of 2,144 nmol/mL.